Unintended consequences and mine closure - Jones, H; Salmon, D (Mine Closure 2012: Seventh International Conference on Mine Closure, 2012)
Many closure plans do not work out as originally conceived and, as a result, some unintended consequences may arise. These consequences can be a result of the techniques employed as part of the closure process, of legislative constraints and of social expectations. In some cases these unintended consequences have major long-term adverse environmental and social outcomes. Conversely in others they have resulted in enhanced environmental and social outcomes for the post-mining use of the mine sites in question. Using examples from around the world the authors outline some unintended consequences and consider the factors that actually influenced the closure outcomes, as against those factors the closure planners apparently envisaged. Based on these examples, the authors then draw conclusions of how the unwanted and unintended consequences could be reduced and the potential societal benefits of closure enhanced through an early, rigorous assessment of closure options.